2020
DOI: 10.1017/s1551929520001327
|View full text |Cite
|
Sign up to set email alerts
|

Development of the Silicon Drift Detector for Electron Microscopy Applications

Abstract: Abstract:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 15 publications
(27 reference statements)
0
4
0
Order By: Relevance
“…Typical silicon drift detectors (SDDs) are only applicable for photon energies up to approximately 15 keV as the quantum efficiency of 500 µm thick silicon rapidly drops for larger energies (see for example Figure 1 in [25]). Strüder et al reported a quantum efficiency that was always above 85% for photon energies between 500 eV and 11 keV for a 450 µm thick SDD [26]. However, as most of the X-ray spectra measured during laser material interactions cover a rather low photon energy range, measurements with an SDD can still provide valuable insights.…”
Section: Spectral X-ray Emissionmentioning
confidence: 99%
“…Typical silicon drift detectors (SDDs) are only applicable for photon energies up to approximately 15 keV as the quantum efficiency of 500 µm thick silicon rapidly drops for larger energies (see for example Figure 1 in [25]). Strüder et al reported a quantum efficiency that was always above 85% for photon energies between 500 eV and 11 keV for a 450 µm thick SDD [26]. However, as most of the X-ray spectra measured during laser material interactions cover a rather low photon energy range, measurements with an SDD can still provide valuable insights.…”
Section: Spectral X-ray Emissionmentioning
confidence: 99%
“…It should be pointed out that µXRF mapping can be time consuming depending on the map area and instrument used. In this study, the average time taken to scan an area of ~100 × 50 mm 2 with the Si(Li) detector at optimised settings was around 2 d. It is anticipated with the newer silicon drift detector (SDD), which is able to collect X-rays at two orders of magnitude faster (Strüder et al, 2020), the total mapping time can be significantly reduced.…”
Section: Discussionmentioning
confidence: 89%
“…Thanks to the researchers' continuous development of SDD in the past 40 years, they are now widely used in space exploration, X-ray spectroscopy, particle physics [6,7], etc. [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%